2015
DOI: 10.1159/000375168
|View full text |Cite
|
Sign up to set email alerts
|

Phospho-p38 MAPK Expression in COPD Patients and Asthmatics and in Challenged Bronchial Epithelium

Abstract: Background: The role of mitogen activated protein kinases (MAPK) in regulating the inflammatory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
1
16
1
Order By: Relevance
“…There was also a trend towards increased CD8 + cell numbers in severe and very severe patients but this did not reach significance according to the Kruskal-Wallis test. COPD patients with chronic bronchitis had a similar number of neutrophils when compared with COPD patients without chronic bronchitis [16,17].…”
Section: Inflammatory Cells In the Bronchial Biopsiesmentioning
confidence: 91%
“…There was also a trend towards increased CD8 + cell numbers in severe and very severe patients but this did not reach significance according to the Kruskal-Wallis test. COPD patients with chronic bronchitis had a similar number of neutrophils when compared with COPD patients without chronic bronchitis [16,17].…”
Section: Inflammatory Cells In the Bronchial Biopsiesmentioning
confidence: 91%
“…Investigations of intracellular molecular signal mechanisms showed that activation of MAPK/NF-κB signal pathways regulates cellular events like differentiation, proliferation, apoptosis and production of pro-inflammatory mediators as well as expression of GPCR in airways (Damera et al, 2012;Gerthoffer and Singer, 2003). In asthmatic patients, there are significant levels of phosphorylated ERK1/2 and p38 MAPK that correlate to the severity of airway disease ( Liu et al, 2008;Vallese et al, 2015). Bradykinin induced the differentiation of normal human lung fibroblasts into myofibroblasts (α-smooth muscle actin [α-SMA] + cells) via bradykinin B2 receptor activation (Vancheri et al, 2005).…”
Section: Bradykinin and Matrix-related Airway Remodellingmentioning
confidence: 99%
“…In our knowledge, data on lung fibroblasts or epithelial cells challenged with radial ESW are not disposable. A second option could be the intratracheal administration of adipose-derived stem cells pretreated with ESW [22,23,48] in the attempt to improve the alveolar septa reparative response in mice with experimentally induced emphysema.…”
Section: Discussionmentioning
confidence: 99%